Physical activity and gut microbiota: a cross-sectional study. (30th September 2020) - Gallè, F; Valeriani, F; Antinozzi, M; Liguori, R; Gianfranceschi, G; Romano Spica, V; Liguori, G; Cattaruzza, MS
Abstract: Background: The composition of gut microbiota, and in particular the intestinal abundance of the two main bacterial phyla of Firmicutes and Bacteroidetes, are associated with human health and diseases and may be conditioned by host and environmental factors such as age, gender and diet. The role of Physical Activity (PA) in determining gut microbiota composition has not been yet completely clarified. A cross-sectional study involving undergraduates from two Italian cities is ongoing to explore this relationship. Methods: Students were invited to provide a fecal sample and to complete the International Physical Activity Questionnaire (IPAQ) in order to define their habitual PA level (inactive, minimally active, health enhancing physical activity -HEPA- active). Demographic and anthropometric information were also collected. DNA from fecal samples was analyzed through the 16S amplicon sequencing. Microbial composition and variability of the samples were evaluated on the light of participants' PA levels. Results: A total of 153 students (47.7% males, mean age 22.4±2.9, mean BMI 22.3±2.7) participated to the study so far. Firmicutes and Bacteroidetes were the main represented phyla. An increase in Firmicutes (58.3±16 to 61.4±13.3, p = 0.68) and a reduction in Bacteroidetes (32.6±14.8 to 30.3±11.4, p = 0.51) have been registered with the increase of PA level. A higher variability (expressed as Shannon α-index) has been detected in minimally active (3.39±0.03) and HEPA-active (3.41±0) individuals respect to inactive subjects (3.35±0.07) (p = 0.05). Conclusions: Even if they are not significant, these preliminary results suggest a relationship between PA levels and gut microbiota composition. An active lifestyle seems to be associated with a greater microbial diversity in the gut. Further researches are needed to explain these findings. Key messages: Physical activity seems to be associated with gut microbiota composition. A greater variability in gut microbiota was found in active people.